Structural, morphological and optical properties of Eu3+ doped ZnO/Zn2SiO4 fabricated via thermal treatment method - Jaafar, Suhail Huzaifa (2021)
The advancement in the electronic display and optical electronics’ technology has made the phosphor field one of the interesting fields to study among researchers. Hence, a lot of new synthesis techniques as well as different starting materials have been used for the fabrication of enhanced phosphor. This research work uses the thermal treatment method to synthesis the Eu3+ doped ZnO/Zn2SiO4 based composites which undergo calcination process at a temperature between 600 °C, 700 °C, and 800 °C for 2 h, 3 h and 4 h holding times. Different parameters or variables have been studied in this work including the effect of calcination temperature, holding time and Eu3+ concentration on the structural, morphological and optical characteristics of ZnO/Zn2SiO4 based composites. The XRD analysis shows the existence of two major phases which are ZnO and Zn2SiO4 crystals, which are supported by the finding in the FTIR. The FESEM micrograph show that progress in the calcination temperature and holding time, affects to the existence of necking-like shape particle. Absorption humps discovered through UV-Vis spectroscopy reveal that samples at the higher calcination temperature, holding time and Eu3+ concentration possess higher absorption intensity. Two types of band gap can be seen from the energy band gap analysis which occurs from ZnO crystal and Zn2SiO4 crystal progress. It is also discovered that the Zn2SiO4 crystal (5.345 to 4.182 eV) has a higher band gap compared to the ZnO crystal (3.217 to 3.176 eV). While, for the photoluminescence study, the emission spectra show higher calcination holding time exhibit higher emission intensity with 700 °C being the optimum temperature. The emission spectra also show higher concentration of Eu3+ helps for enhancing the emission intensity until 5 mol% of Eu3+ dopant concentration. The study findings provide a new and simple method for the fabrication of Eu3+ doped ZnO/Zn2SiO4 based composites for new potential red phosphor application in the optoelectronic fields.